A Systematic Review of Virtual Reality Applications in Engineering Education: Methodologies, Assessments, and Outcomes - Hernandez, Susana Schlosser; Hernandez, Matheus Nicolás; Camillo, Bruna Zappelino; Padilha, Fabiana Regina Rezende (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
This systematic review investigates how Virtual Reality (VR) has been applied in engineering education, which assessment strategies are employed to measure its effectiveness, and what main outcomes have been reported. Fourteen recent studies were selected and analyzed, with findings categorized into three dimensions: learning performance, student engagement and motivation, and usability and user experience. Results indicate significant gains in academic performance, with average test-score increases ranging from 15% to 17% in VR activities. Immersive VR environments also enhanced students’ attention and involvement, as evidenced by both objective indicators (EEG data) and subjective feedback. Despite these benefits, recurrent challenges include physical discomfort, technical limitations, cognitive navigation difficulties, and a short-lived novelty effect. High infrastructure costs and the need for continuous content updates further hinder large-scale adoption. The discussion emphasizes the need to balance pedagogical advantages, operational feasibility, and sustained engagement. Future work should explore VR implementations in resource-constrained, regular classroom settings and conduct economic analyses comparing VR laboratories to traditional teaching approaches. When supported by careful instructional design, appropriate infrastructure, and engagement strategies, VR shows solid potential to enhance engineering education.